For the love : fighting for grace in a world of impossible standards - Hatmaker, Jen (Nelson Books, 2015)
"Bestselling author Jen Hatmaker is convinced life can be lovely and fun and courageous and kind. She knows how the squeeze of this life can make us competitive and judgmental, how we can lose love for others and then for ourselves"--Jacket.